Epidemiological characteristics of respiratory diseases in emergency department patients from different ethnic groups in the Atushi region, Xinjiang - Jin Ma; Xiaolong Zhu; Qi Tang; Shifang Liu; Weiwei Zhou (Frontiers in Medicine)
The Xinjiang region of China has long been a high-prevalence area for respiratory diseases, especially pulmonary tuberculosis and chronic obstructive pulmonary disease (COPD). This retrospective, cross-sectional study aimed to analyze the epidemiological characteristics of patients visiting the emergency department (ED) of the People’s Hospital of Atushi in Xinjiang, China, from January to December 2024. This study focused on the prevalence and distribution of respiratory diseases. A total of 8,837 patients were included, and respiratory diseases emerged as the most prevalent condition, accounting for 35.2% of the cohort. The leading respiratory conditions were acute upper respiratory infections (18.4%), pulmonary tuberculosis (4.1%), and COPD (4.6%). Respiratory diseases were significantly more common in older patients and were associated with both gender and ethnicity, with the Uygur ethnic group showing the highest prevalence. The findings suggest that age, gender, ethnicity, and environmental factors, such as the region’s climate, play pivotal roles in the epidemiology of respiratory diseases. These results underscore the need for targeted public health interventions aimed at managing respiratory conditions, especially for vulnerable populations such as the elderly and ethnic minorities in Xinjiang, China.